The effects of ethyl acetate fraction of Ananas Comosus (L.) Merr. of tongue cancer cell growth inhibition Supri’s Clone-1, invitro - Maureen Martina; Roosje Rosita Oewen; Eriska Riyanti; Achmad Syawqie; S. Supriatno (Padjadjaran Journal of Dentistry, 2011)
Ananas comosus (L.) Merr has several purposes which include antioxidant and anti-inflammatory activity that shows some pharmacological effects and the subject of anti-cancer or anti-cancer supporting material. The research objective was to analyze the effects of ethyl acetate fraction of Ananas comosus (L.) Merr. of tongue cancer cell growth inhibition Supri’s clone-1 (SP-C1). This type of study was a research laboratory. Next, cell growth inhibition testing by the ethyl acetate fraction of Ananas comosus (L.) Merr. with various concentrations (0; 62.5; 125; 250; 250; 500 and 1000 microgram/ml) using the MTT assay test. Growth barriers identified by Biorad microplate tool reader with a wavelength of 540 nm. The number of SP-C1 cells examined was 2 x 104 cells/wells with incubation time 24 and 48 hours. Data were analyzed using a two-ways ANOVA followed by post hoc test (LSD test) with 95% significance level. The results showed ethyl acetate fraction of Ananas comosus (L.) Merr. able to inhibit the growth of cancer cells SP-C1. Various concentrations of ethyl acetate fraction of pineapple were highly significant, meaning that the concentration effect on cell growth of SP-C1. Similarly, incubation time effect on the growth of SP-C1 cells that were very meaningful. The biggest obstacle effect of ethyl acetate fraction of Ananas comosus (L.) Merr. occurred at a concentration of 1000 ug/ml (43.45%) with an incubation time of 48 hours. Conclusion of this study was the fraction of ethyl acetate Ananas comosus (L.) Merr. has the effect of inhibiting the growth of cancer cells SP-C1.